Stereotactic Radiotherapy in Uveal Melanoma - Ela Delikgöz Soykut; Ayşen Dizman; Yıldız Yükselen Güney (Türk Oftalmoloji Dergisi, 2014)
Uveal melanoma is the most common primary malignant intraocular neoplasm in adults. The aims of treatment of the uveal melanoma are to prevent the metastatic spread of the disease and to preserve as much useful vision as possible. Although enucleation has been the traditional treatment of uveal melanoma until the mid-20th century, the impact of surgical removal of the eye on survival remains unclear. Because of the permanent loss of the eye and vision, many globe sparing treatment methods has been developed. Nowadays, radiotherapy has replaced enucleation as the treatment of choice. Episcleral plaque radiotherapy and charged particle radiotherapy are the most studied modalities. More recently, stereotactic radiotherapy is being used, however, no long-term data are available. (Turk J Ophthalmol 2014; 44: Supplement 35-42)